Analysis of Light‐Enhanced Capacitance Dispersion in Perovskite Solar Cells - Hernández‐Balaguera, Enrique; Romero, Beatriz; Najafi, Mehrdad; Galagan, Yulia (Advanced materials interfaces, 2022)
Interface engineering has become one of the most important research strategies to harness the full potential of perovskite solar cells. Photovoltaic community seems to herald the imminent development of 30% efficient perovskite devices with competitive lifetimes, subject, among other aspects, to clarify “what happens under the interfaces.” One of the most powerful techniques to characterize the intermixing ionic‐electronic processes that take place at perovskite interfaces is the Impedance Spectroscopy. It is a real fact that this methodology reveals the characteristic phenomenology attributed to interfacial phenomena, in form of complex spectra that interfere with a proper identification of dominant mechanisms. This article presents approaches to characterizing the non‐ideal electrical properties associated with the appearance of an interfacial capacitance distribution, identifying major sources of intrinsic/extrinsic origin and so, providing further progress in the understanding of phenomenological mechanisms of photovoltaic perovskites. Importantly, the study addresses the evolution of dispersive capacitance's characteristic parameters with light intensity (and bulk thickness), obtaining a useful alternative way of determining the ideality factor and thus, the recombination of charge carriers. The results are discussed in light of critical importance exhibited by the interactions between ionic and electronic species, with the aim of advancing in device efficiency and stability. The emergence of dispersive capacitances in the electrical modeling of perovskite solar cells is a real fact impossible to ignore for the photovoltaic community. Here, a detailed modeling and understanding of characteristic parameters of non‐ideal interfacial capacitance including their evolution with light intensity and active layer morphology is provided, with the aim, on the horizon, to control device degradation mechanisms.